CONCEPTUAL INCLUSIVE PUBLIC SERVICE IN INDONESIA GOVERNMENT - Zainudin, Arif; Arfiani, Yuni; Mumpuni, Sesya Dias (CosmoGov: Jurnal Ilmu Pemerintahan, 2022)
Experts have widely discussed the concept of inclusive service, and governments in various countries have widely applied this concept. However, there is still much discrimination in the facility's people with disabilities (PWD) sector. Thus this paper aims to concept measurement models and parameters of inclusive public services to people with disabilities (PWD). The method of this paper is reviewing the previous research with a high impact score. Then the result of the data presented uses CiteSpace analysis to prioritize concept inclusive model and parameters in public services. The results of the research are the model and parameters of inclusive public services to PWD are openness, fairness, infrastructure, and responsiveness. It required content of the government services to meet the needs of PWD. The paper includes implications satisfaction for an inclusive model in the Indonesia Government and managing inclusivegb777